Analisis Implementasi Kebijakan Pendidikan Sabtu Budaya di MI NW Tanak Beak - Bariah Bariah; Yudin Citriadin; Abdulloh Fuadi (PALAPA, 2023)
Today students' knowledge of local culture is getting weaker. Schools need to carry out policies to increase cultural awareness to students. The purpose of this study was to analyze the implementation of the Cultural Saturday education policy at MI NW Tanak Beak. This study uses a qualitative approach. Data collection was carried out through interviews, observation, and documentation. This study involved school principals, teachers, and parents as informants. The results of the study show that the implementation of the cultural Saturday policy is carried out through the development of traditional games and folk songs as well as inculcating habits in daily activities. In every traditional game and regional song, character values always appear, such as the value of togetherness, the value of tolerance, the value of responsibility, the value of discipline, the value of never giving up, thoroughness, and so on. School support in implementing a culture-based education curriculum includes the participation of school members and the existence of school rules (norms). School participation includes the participation of school principals, teachers, and school committees who have carried out education by their respective duties. The obstacles to implementing a culture-based education curriculum at MI NW Tanak Beak are as follows: first, the assessment process with a lot of administration so that time is hampered in observing children, second, factors from within students include fear and difficulties that arise at the beginning when trying the game traditional culture, as well as complaints in the form of fatigue and lack of enthusiasm in participating in cultural activities, third, technological developments that result in children being more likely to spend their time gadget fourth, limited funds, and fifth, lack of cooperation from parents.